Thermal dynamics of ovarian maturation in Atlantic cod (Gadus Morhua) - Kjesbu, Olav Sigurd; Righton, David; Krüger-Johnsen, Maria; Thorsen, Anders; Michalsen, Kathrine; Fonn, Merete; Witthames, Peter R. (Canadian Journal of Fisheries and Aquatic Sciences, 2010)
The timing and success of spawning in marine fish are of fundamental importance to population persistence and distribution and, for commercial species, sustainability. Their physiological processes of reproduction are regulated, in part, by water temperature, and therefore changes in marine climate may have dramatic effects on spawning performance. Using adult Atlantic cod (Gadus morhua) as a case study, we examined the links between water temperature, body size, vitellogenesis, and spawning time by conducting extensive laboratory and field studies. Our experiments documented that vitellogenesis generally starts at autumnal equinox and that oocyte growth and investment are greater in cod held at warmer temperatures. Furthermore, spawning occurred earlier when oocyte growth was more rapid. Large females spawned earlier than smaller females at warmer temperatures, but this effect vanished at colder temperatures. The experimental results were confirmed by measurements of oocyte growth collected from wild-caught cod in northern (Barents Sea) and southern (Irish Sea and North Sea) populations. The established, general model of oocyte maturation was consistent with published egg production curves of cod from these waters, considering relevant in situ temperatures recorded by individual data-storage tags on cod. These findings have considerable relevance for future studies of fish recruitment in relation to climate change.